Hidroeléctrica do Cávado 1945-1964. Uma ideia de paisagem na arquitectura de Januário Godinho - MOREIRA, César Machado (2012)
Among many transformations that occur in the territory, some are provoked conscientiously and correspond to cultural and social acts, nominally public works, as there are the hydroelectric exploitations and the human settlements that follow them. In the urban and territorial landscape developed for the five exploitations of HICA analysis, it’s evident in the architecture the pragmatism of its conception and the Januário Godinho architecture sensibility “to the landscape rusticity”. As per the specific character of each of the pre settled programs for each place, the architect made the correlation with a distinct solution “in the perfect balance between the classicism and the modernity, industry and nature” where “it results the impression in the option of recognize the specific character of each one of the places, to delineate its preferences and actions”. First, through three options to read the landscape (the desired landscape, the practiced landscape and the materialized landscape), we explain the methodology we are using to understand the meaning of transformation operated by Januário Godinho architecture in the Cávado landscape recognizing the history of hydroelectric and using the debate around its location and the general lines of its development. Secondly, through a practical application, we use the first of exploitations made, the Venda Nova to exemplify this process of landscape construction in Cávado.